2022
DOI: 10.1126/sciimmunol.ade5686
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 is inactivated by the acidic pH environment of tumors enabling engineering of a pH-selective mutein

Abstract: Cytokines interact with their receptors in the extracellular space to control immune responses. How the physicochemical properties of the extracellular space influence cytokine signaling is incompletely elucidated. Here, we show that the activity of interleukin-2 (IL-2), a cytokine critical to T cell immunity, is profoundly affected by pH, limiting IL-2 signaling within the acidic environment of tumors. Generation of lactic acid by tumors limits STAT5 activation, effector differentiation, and antitumor immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…The importance of the TME on TIL dynamics is further proven by the effect of hypoxia and acidity on TIL effector functions and proliferation. It has been suggested that an acidic environment prevents lymphocyte proliferation by impairing the stimulatory activity of IL-2 [76,116,117]. Furthermore, acidosis in the TME impairs the cytolytic activity and cytokine secretion of CD8 + T lymphocytes [76,118].…”
Section: Search Strategymentioning
confidence: 99%
“…The importance of the TME on TIL dynamics is further proven by the effect of hypoxia and acidity on TIL effector functions and proliferation. It has been suggested that an acidic environment prevents lymphocyte proliferation by impairing the stimulatory activity of IL-2 [76,116,117]. Furthermore, acidosis in the TME impairs the cytolytic activity and cytokine secretion of CD8 + T lymphocytes [76,118].…”
Section: Search Strategymentioning
confidence: 99%
“…Last, gene modifications developed for CAR-T cell therapies to overcome tumor-related immunosuppression could also be used for TCR-T cells, such as PD-1 disruption, PD-1–CD28 chimeric constructs, or dominant negative transforming growth factor–β receptor type 2 ( 116 ). In addition to synthetic biology, combination with approaches targeting the tumor microenvironment ( 7 , 8 ) or modified cytokines resistant to hypoxic and acidic conditions prevalent in tumors may improve the efficiency of adoptive T cell therapies ( 117 ).…”
Section: Perspectives: Next Steps In T Cell Engineeringmentioning
confidence: 99%
“…Leveraging differential pH levels within the TME for conditional activation has also been explored. Gaggero et al recently demonstrated the pH sensitivity of the wild‐type IL‐2/IL‐2Rɑ interaction 93 . At acidic pH (6.5, commensurate with tumor levels), IL‐2 is shown to be a much weaker agonist of activated CD8 T cells because of minimized IL‐2Rɑ binding (IL‐2RβƔ was unchanged) 93 .…”
Section: Spatial Programming Via Tumor‐specific Stimuli—conditional R...mentioning
confidence: 99%
“…Using yeast surface display and directed evolution, the authors identify Switch‐2, an IL‐2 mutein with 5 amino acid mutations capable of binding IL‐2Rɑ at low pH. Switch‐2 is shown to improve responses in a variety of tumor models over extended half‐life Fc/IL‐2 93 . The pH dependency of the high affinity IL‐2Rɑ interaction has interesting applications for IL‐2 therapies, since it implies that wild‐type IL‐2/lymphocyte interactions in the tumor are naturally not‐alpha.…”
Section: Spatial Programming Via Tumor‐specific Stimuli—conditional R...mentioning
confidence: 99%
See 1 more Smart Citation